Implementation of Scientific Approach for Teaching English at SMA Negeri 1 Baturetno in 2014/2015 Academic Year - Julianto, Wahyu, Prof. Dr. Endang Fauziati, M. Hum, Mauly Halwat Hikmat, Ph. D (2015)
This research is aimed at observing teaching of English at SMA Negeri 1 Baturetno in 2014/2015 academic year. The objectives of the study are to describe and to explain the implementation of scientific approach for teaching English at SMA Negeri 1 Baturetno. The type of the study is descriptive qualitative research especially naturalistic approach. In this research, the data derived from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview and documentation. Techniques for analyzing data are reduction of the data, display of data, and conclusion or verification. The results of the study are: (1) There are general learning objective and specific learning objective in teaching English. (2) Classroom procedure used Observing, Questioning, Experimenting, Associating, Communicating, with different patterns. (3) Classroom techniques used in teaching English are reading with understanding, reading comprehension, grouping, questioning session, discussion, role-play, and exercise modelling. (4). The roles of instructional materials are as a source of activities for learner practice and communicative interaction, as a reference source for learners on grammar, vocabulary, pronunciation, etc, as a syllabus, a source of stimulation and ideas for classroom language activities, and a resource for self directed learning or self-access work. (5) The English teacher roles are as facilitator, manager, explainer, source of knowledge, inquiry controller, and group organizer. (6) The learner roles are as the member of a group, as the tutor of other learners, the learner learns from English source, English teacher, other teaching sources, and other students. (7) The medias used by the English teachers are over head projector (OHP), board, laptop, and video. (8) The assessments are conducted in authentic assessment, daily test, portfolio based-assessment, and midterm test. Keywords: scientific approach, teaching of English, learning English